Higher UV-shielding ability and lower photocatalytic activity of TiO2@SiO2/APTES and its excellent performance in enhancing the photostability of poly(p-phenylene sulfide). Issue 35 (19th April 2017) - Bai, Yali; Li, Zhenhuan; Cheng, Bowen; Zhang, Maliang; Su, Kunmei
Abstract : U–TiO2 is successfully coated with SiO2 and subsequently well modified by APTES, and a core–shell structure exists on TiO2 @SiO2 and TiO2 @SiO2 /APTES, which greatly reduces aggregation of the TiO2 nanoparticles. Abstract : U–TiO2 is successfully coated with SiO2 and subsequently well modified by APTES, and the core–shell structure exists on TiO2 @SiO2 and TiO2 @SiO2 /APTES, which greatly reduces aggregation of the TiO2 nanoparticles. The photocatalytic activities of U–TiO2, TiO2 @SiO2, and TiO2 @SiO2 /APTES are evaluated using MB decomposition. Nearly 50% of the MB is degraded after 15 min in the presence of the U–TiO2 under UV radiation (300 W), and only 17.44% and 4.18% of the MB is degraded in the presence of the TiO2 @SiO2 -0.6 and TiO2 @SiO2 /APTES-1. However, TiO2 @SiO2 /APTES-0.6 and TiO2 @SiO2 -0.2 exhibit excellent UV absorbance capacities, and the TiO2 @SiO2 /APTES-0.6 achieves 80% of the UV-shielding ability of U–TiO2 . Poly( p -phenylene sulfide) (PPS) is an easily photodegraded material and TiO2 /PPS is more seriously photodegraded than PPS, however, the TiO2 @SiO2 /APTES nanoparticles can effectively protect the PPS from UV degradation, owing to their lower photocatalytic activities, higher UV-shielding abilities and easy dispersion in the PPS matrix. The breaking strength retention rate of the 1 wt% TiO2 @SiO2 /APTES/PPS film shows a maximum increase of 38.26%, and the breaking elongation retention rate increased by 41.64% at 2 wt% TiO2 @SiO2 /APTES loading. These results reveal that the incorporation of the TiO2 @SiO2 /APTES nanoparticles into the PPS matrix imparts excellent anti-UV properties to the PPS matrix, leading to a mechanical performance improvement.